Smoking behaviour and nicotine addiction of individuals working in adana tekel cigarette factory - Aksakal, Ayşe; Khorshid, Leyla (Journal of Dependence, 2006)
Objective: Processing of tobacco leaves generates a lot of dust and liberates volatile components of tobacco. Exposure to tobacco dust is known to affect the respiratory tract in humans. It has been observed that smoking prevalence among the tobacco factory workers is high and the trend of cessation is low. This descriptive study was carried out to determine smoking behaviour, smoking cessation, nicotine addiction and relationship of these with some variables in the individuals working in Adana Tekel Cigarette Factory. Method: The sample consist of 500 individuals working in Adana Tekel Cigarette Factory. Data was collected by using a questionnaire including questions on demographic characteristics, smoking and Fager-ström Nicotine Dependence Test. Chi-square test was used in analysing the data. Results: It was found that 56% of individuals were current smoker. Smoking cessation prevalence was 17.5%. Nicotine addiction varies by gender and department. Women workers have a low nicotine addiction. Smoking cessation prevalence varies by educational level and department. It was determined that prevalence of the heaviest nicotine addiction was lower in women workers than men. Conclusion: Smoking prevalence and nicotine addiction was high in the individuals working in cigarette factory. The results suggest that the individuals working in cigarette factory should be given prority in the fight against smoking.